La soledad contigo (1960) by Pilar Paz Pasamar: Chronicle of a Female Confinement - Medina Puerta, Carmen (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article approaches the intimate and domestic universe of La soledad contigo (1960), a book that Pilar Paz Pasamar devoted to her married life. An interdisciplinary methodology is taken place. On the one hand, the author life is presented by using History, Sociology, and Gender Studies. On the other hand, this book of poems is analyzed in the light of the statements and interviews that the writer gave throughout her life. In addition, this study establishes a comparison with the poetic works of contemporary women writers in which the theme of motherhood also appears as a literary topic. In summary, this essay examines the feminine role, linked to reproductive work, in Franco’s society, through the poetic testimony of Pilar Paz Pasamar.